Climate-Smart Villages in Haryana, India - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Maize and Wheat Improvement Center (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This report by CCAFS and CIMMYT highlights some early evidence from Climate-Smart Villages in Haryana. It gives an overview of the adoption of climate smart agriculture in Karnal district of Haryana. Climate Smart Villages are sites where farmers, researchers, and local government partners and the private sector come together to understand which climate smart agriculture practices are best suited for a particular location. A portfolio of interventions are chosen that will increase farmers’ incomes through higher productivity, while building their resilience to extreme and variable climatic events. The interventions aim to reduce greenhouse gas emissions and thus ensure that resources are used sustainably.